2004
DOI: 10.1002/bdrc.20009
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial transcriptional interaction within the cardiac neural crest: A pair of HANDs in heart formation

Abstract: The cardiac neural crest migrate from rostral dorsal neural folds and populate the branchial arches, which directly contribute to cardiac-outflow structures. Although neural crest cell specification is associated with a number of morphogenic factors, little is understood about the mechanisms by which transcription factors actually implement the transcriptional programs that dictate cell migration and later the differentiation into the proper cell types within the heart. It is clear from genetic evidence that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 108 publications
(133 reference statements)
0
11
1
1
Order By: Relevance
“…Although Hand1 and Hand2 are normally downregulated during embryogenesis by E13.5 and undetectable in newborns [6, 15, 16, 47], we did not detect any prolonged ectopic Hand2 expression in stillborn knock-in mutant hearts. Similarly, chamber-restricted gene Tbx20 also was not ectopically misexpressed, suggesting that Nppa and Ncx1 upregulation are indicative of heart failure rather than chamber identity/morphologic abnormalities.…”
Section: Resultscontrasting
confidence: 61%
See 2 more Smart Citations
“…Although Hand1 and Hand2 are normally downregulated during embryogenesis by E13.5 and undetectable in newborns [6, 15, 16, 47], we did not detect any prolonged ectopic Hand2 expression in stillborn knock-in mutant hearts. Similarly, chamber-restricted gene Tbx20 also was not ectopically misexpressed, suggesting that Nppa and Ncx1 upregulation are indicative of heart failure rather than chamber identity/morphologic abnormalities.…”
Section: Resultscontrasting
confidence: 61%
“…Hand factors show high amino acid identity between species, suggesting conserved biologic function [6, 8, 9, 14, 15, 39], whereas functional studies have shown that Hand1 and Hand2 exhibit broad dimerization profiles [17]. Hand1 and Hand2 are evolutionarily conserved basic transcription factors that exhibit dynamic and partially overlapping spatiotemporal expression patterns during cardiovascular development.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The bHLH factors Hand1 and Hand2 are members of the Twist-family of proteins and are broadly expressed throughout development in a number of tissues including: neural crest that contribute to craniofacial structures, sympathetic and enteric neurons and cardiac outflow tract (OFT); developing limbs; extraembryonic tissues; placenta and most significantly the cardiomyocytes [12, 13]. Hand mRNA is first detected around E7.5 throughout the cardiac crescent [8, 9, 22, 43].…”
Section: Hand1 and Hand2 Transcription Factors And Cardiovascular Devmentioning
confidence: 99%
“…Mirroring the complex roles and derivatives of the NC, numerous congenital anomalies and syndromes have been mapped to defects in NCC function (Firulli and Conway, 2004; Verzi et al, 2007; Conway and Kaartinen, 2011; Bonilla-Claudio et al, 2012). Cranial NC abnormalities have been identified in patients with thymic aplasia (Ohnemus et al, 2002), palate defects (van Limborgh et al, 1983), and craniofacial malformations (Conway and Kaartinen, 2011).…”
Section: Introductionmentioning
confidence: 99%